Influência da opacidade da resina composta utilizada na anatomização de pinos de fibra na resistência de união à dentina intrarradicular - Gomes, Matheus Henrique [UNESP] (2017)
The aim of this study was to evaluate the push-out bond strength between fiber glass posts customized with different composite resin opacities to intraradicular dentin. Thirty uniradicular premolars were submitted to endodontic treatment, divided into three groups (n=10), according to the type of intraradicular retainer: fiber glass posts customized with translucent composite resin, fiber glass posts customized with opaque composite resin and non-customized fiber glass posts. The samples were sectioned in slices of approximately 1.3mm of each region to be analyzed (cervical, middle and apical) and then submitted to the push-out test. The bond strength data (MPa) were submitted to two-way repeated ANOVA and Tukey's test (p=0.05). The results showed that the bonding strength of fiber glass posts to dentin was influenced by the customization with composite resin as well as its opacity. The use of translucent composite resin presented higher values of bond strength compared to opaque composite resin in the cervical third, resulting in a more efficient method for the customization of fiber glass posts